2017
DOI: 10.1002/rcs.1851
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of operative outcomes between standard and robotic laparoscopic surgery for endometrial cancer: A systematic review and meta‐analysis

Abstract: BackgroundEvidence has been systematically assessed comparing robotic with standard laparoscopy for treatment of endometrial cancer.MethodsA search of Medline, Embase and Cochrane databases was performed until 30th October 2016.ResultsThirty‐six papers including 33 retrospective studies, two matched case–control studies and one randomized controlled study were used in a meta‐analysis. Information from a further seven registry/database studies were assessed descriptively. There were no differences in the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 54 publications
5
43
0
Order By: Relevance
“…Importantly, the available data show no difference in survival or rates of recurrence between patients with endometrial cancer undergoing a total laparoscopic hysterectomy and those treated by laparotomy . Compared with laparoscopy, robotic surgery may have benefits because the operating time, blood loss, hospital stay and rate of conversion to laparotomy are lower, although the cost remains prohibitive for many hospital trusts . There are currently insufficient data to inform the safest choice of surgical route in women with a BMI greater than 50 kg/m 2 , for whom conversion rates are much higher than for women with a lower BMI …”
Section: Treating Obese Women With Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the available data show no difference in survival or rates of recurrence between patients with endometrial cancer undergoing a total laparoscopic hysterectomy and those treated by laparotomy . Compared with laparoscopy, robotic surgery may have benefits because the operating time, blood loss, hospital stay and rate of conversion to laparotomy are lower, although the cost remains prohibitive for many hospital trusts . There are currently insufficient data to inform the safest choice of surgical route in women with a BMI greater than 50 kg/m 2 , for whom conversion rates are much higher than for women with a lower BMI …”
Section: Treating Obese Women With Endometrial Cancermentioning
confidence: 99%
“…34,35 Compared with laparoscopy, robotic surgery may have benefits because the operating time, blood loss, hospital stay and rate of conversion to laparotomy are lower, although the cost remains prohibitive for many hospital trusts. [36][37][38] There are currently insufficient data to inform the safest choice of surgical route in women with a BMI greater than 50 kg/m 2 , for whom conversion rates are much higher than for women with a lower BMI. 39,40 Few studies have compared the yield of pelvic and paraaortic lymph nodes in obese patients with endometrial cancer undergoing different modalities of surgery, although fewer lymphadenectomies appear to have been attempted in women with an extremely high BMI, by any surgical route.…”
Section: Diagnosing Endometrial Cancer In Obese Womenmentioning
confidence: 99%
“…Other studies also demonstrate this, but the transfusion rate in the open arm of this series is higher than some other reports and might be a confounding factor. For endometrial cancer, a reduction in the number of conversions to laparotomy has been demonstrated . In this study, a lower conversion rate has not been shown possibly due to the lower number of comorbidities in patients with cervical cancer compared with endometrial neoplasias.…”
Section: Discussionmentioning
confidence: 56%
“…3 Lymph node count (n)-median (range) 15 However, one previous study found the robotic approach to be more expensive 10 while another reported similar costs compared with OS once a surgeon had experience of over 30 cases. 22 Although many have suggested that introducing robotics might increase the cost of surgery 23 This study has demonstrated improvements in blood loss and blood transfusions, complications, and days stay in hospital with the introduction of a robotic service into an institution. Other studies also demonstrate this, 1 but the transfusion rate in the open arm of this series is higher than some other reports and might be a confounding factor.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation